Advancements in Medical Devices for Surgical Precision: Exploring the Role of Robotics, AI, and Minimally Invasive Technologies - Majeed, Aya Rfaat; Hassan Ali, Aseel Falah; Hassan, Mohammed Qasim; Ghareeb, Mohammed Jawhar; Kakarash, Mohammed Fuad (American Journal of Botany and Bioengineering, 2025)
This weighs heavily upon my shoulders every single day; therefore, my success is intertwined with their success. Moving forward, the page will showcase a variety of differing thoughts and perspectives regarding this latest piece of work and its implications. Generally, academicians are encouraged to establish a robust foundation composed of solid references, be clear about their ultimate end goals, and present a unique perspective along with innovative solutions for the evolving future of health care. By doing so, they can effectively contribute to the advancement of the field.